Development of a Benzimidazole‐Derived Bidentate P, N‐Ligand for Enantioselective Iridium‐Catalyzed Hydrogenations. Issue 2 (19th November 2013) - Weemers, Jarno J. M.; Sypaseuth, Fanni D.; Bäuerlein, Patrick S.; van der Graaff, William N. P.; Filot, Ivo A. W.; Lutz, Martin; Müller, Christian
Abstract: The development of a novel benzimidazole‐derived bidentate P, N‐ligand and its application in Ir‐catalyzed hydrogenation is described. The ligand backbone was obtained through a one‐pot tandem hydroformylation–cyclization sequence and the enantiomers of the generated alcohol were separated by chiral HPLC. By comparing the experimentally obtained CD spectra of the enantiomers with the simulated spectra generated from time‐dependent DFT calculations, the absolute configuration could be obtained. The chiral alcohols could further be isolated on a larger scale after transesterification by using Candida Antarctica lipase B (Novozym 435) and could subsequently be converted into the corresponding chiral P, N‐ligand by reaction with ClPPh2 . The coordination properties of the racemic P, N‐ligand were investigated and the molecular structure of the Rh I complex [(P, N)Rh(CO)Cl] was determined by X‐ray crystal structure analysis. The corresponding chiral cationic Ir I complex was used as catalyst for the enantioselective hydrogenation of prochiral N ‐phenyl‐(1‐phenylethylidene)amine and trans ‐α‐methylstilbene. For the N ‐aryl‐substituted imine, enantiomeric excesses of only 10 % were obtained, whereas the unfunctionalized olefin could be hydrogenated with enantiomeric excesses of up to 90 %. Interestingly, the modular synthetic access to the P, N‐hybrid system described here allows facile modification of the ligand structure, which should extend the scope of such novel P, N‐ligands for asymmetric catalytic conversions to a large extent in the future. Abstract : We report on the development of a novel bidentate P, N‐ligand with a benzimidazole‐based backbone obtained through a one‐pot tandem hydroformylation–cyclization reaction. The chiral ligand was successfully applied in Ir‐catalyzed hydrogenation reactions in which enantiomeric excesses of up to 90 % could be obtained.